Performance on a Motor Control Test in an Asymptomatic Adolescent Population - Kari Lindegren; Kristin Bastian; Christopher Kovacs; Robyn McHugh; Catherine Quatman-Yates; Mark Paterno (North American Sports Medicine Institute, 2022)
# Background Low back pain is a condition present during both adulthood and adolescence. Adolescents with low back pain may benefit from treatment focused on improving abdominal muscle performance and motor control. The supine double leg lowering test (SDLLT) may be a reliable measure to assess core stability in adults, but adolescent performance on the SDLLT has not yet been established in the literature. # Purpose To examine performance on the SDLLT in healthy adolescents ages 13 to 18 years and describe influences of gender, age, body mass index, and participation in sport. # Study Design Cross-Sectional Study # Methods Four licensed physical therapists administered the SDLLT with a Stabilizer pressure biofeedback cuff and inclinometer in 90 adolescents without low back pain (females = 41, males = 49) from three schools in a mid-western metropolitan area. Descriptive statistics, independent sample t-tests, two-way analysis of variance, and Pearson correlation coefficients were utilized to analyze the data. # Results Average SDLLT score was 72.36 +/- 12.54 degrees. A significant difference between SDLLT score was present between genders with males performing better than females. No interactions between performance and involvement in sport were demonstrated. # Conclusions Female and male adolescents appear to perform differently on the SDLLT with a stabilizer and appear to perform worse than scores recorded for adults. The SDLLT may be used to measure motor control in adolescents, but clinicians should utilize age-appropriate data for clinical decision making. # Levels of Evidence Level 2c